Voxel-wise meta-analysis of gray matter abnormalities in idiopathic Parkinson's disease - Pan, P. L.; Song, W.; Shang, H. F. (European journal of neurology, 2012)
Structural neuroimaging studies on idiopathic Parkinson’s disease (IPD) with voxel‐based morphometry (VBM) yielded variable and conflicting findings. A systematic review of VBM studies of patients with IPD and healthy control (HC) subjects published in PubMed, ISI Web of Science, Embase, and Medline databases from 1995 to 25 October 2010 was conducted. Coordinates were extracted from clusters of significant gray matter (GM) difference between patients with IPD and HC subjects. Meta‐analysis was performed using signed differential mapping. A total of 17 VBM studies involving 498 patients with IPD and 375 HC subjects met the inclusion criteria. A significant regional GM volume decrease was detected in the left inferior frontal gyrus (BA47) extending to the left superior temporal gyrus (BA38) and the left insula (BA13) of patients with IPD compared with HC subjects. The findings of this study remain largely unchanged in quartile and jackknife sensitivity analyses and in subgroup analyses. Robust GM reductions in the inferior frontal/orbitofrontal gyrus (BA47) are implicated in IPD, and the reductions may be related to the mediation of the non‐motor IPD symptoms, such as cognitive, emotional, and autonomic functions. Further studies must be conducted to determine whether the findings are specific to all IPD subtypes or different from the atypical Parkinsonism.